Institutional economics and its relationship with productive sectors - Artavia Jiménez, María Leonela (2018)
Institutional economics theory regarding its relationship with productive sectors is discussed in this article. The main objective of the paper is to clarify the main contributions of institutionalism theory in the formulation of policies to support the productive sectors of developing countries. To this end, the article discusses the role of the State as a regulatory entity, public goods, and the importance of institutions in the socio-economic order of the country. From this analysis, it is concluded that one of the routes to strengthen the productive development of developing countries is having greater institutional development for two purposes: first towards the promotion of the integral development of people, who make up the society and are part of the workforce, and second towards the promotion of innovative dynamics that would include the implementation of new technologies.